Quantification of run-of-river hydropower potential in the Upper Indus basin under climate change - Dhaubanjar, Sanita; Lutz, Arthur F.; Smolenaars, Wouter Julius; Khanal, Sonu; Jamil, Muhammad Khalid; Biemans, Hester; Ludwig, Fulco; Shrestha, Arun Bhakta; Immerzeel, Walter W. (Frontiers in Water, 2023)
Despite ambitious plans to quadruple hydropower generation in the Indus basin, a quantitative assessment of the impact of climate change on hydropower in the basin is missing. To address this gap, we combine downscaled CMIP6 projections with the Hydropower Potential Exploration (HyPE) model to quantify future hydropower potential in the upper Indus basin. HyPE uses a spatial cost-minimization framework to evaluate four classes of hydropower potential, namely theoretical, technical, financial and sustainable, considering various constraints on the siting and sizing of two run-of-river hydropower plant configurations. Under future discharge projections, all Dhaubanjar et al. Future hydropower potential in the upper Indus basin address the complexity of achieving sustainable and equitable hydropower development in the Indus basin under such spatial mismatch between hydropower availability and energy demand in a resource-limited world.